The Effects of Fire Academy Training and Probationary Firefighter Status on Select Basic Health and Fitness Measurements - Lan, Fan Yun; Yiannakou, Ioanna; Scheibler, Christopher; Hershey, Maria Soledad; Cabrera, Juan Luis Romero; Gaviola, Gabriel C.; Fernandez-Montero, Alejandro; Christophi, Costas A.; Christiani, David C.; Sotos-Prieto, Mercedes; Kales, Stefanos N. (My University, 2021)
Purpose This study aimed to investigate changes in firefighter recruits' select health and fitness measurements, from academy training to the early probationary firefighter period. Methods Firefighter recruits from two New England fire academies were followed up prospectively from enrollment at the academy to graduation after 15- to 16-wk training programs, and then for an average of 8 months as probationary firefighters. The participants' demographic, lifestyle, and mental health information was collected using a questionnaire. Body mass index, percent body fat, blood pressure, and push-ups were also measured at each time point. Furthermore, the academies tested the recruits on selected fitness measures (push-ups, pull-ups, and 1.5-mile running time) at academy entry, midtraining, and at graduation. Results Ninety-two recruits consented and were included in the analyses. The recruits' percent body fat significantly decreased (median, 21.0%-18.2%) from baseline to graduation, and push-up capacity significantly improved (median, 34-53 per minute) in the same period, along with pull-ups and 1.5-mile running time. However, the recruits' blood pressure, both systolic and diastolic, increased significantly by an average of 3 mm Hg during the training. Those completing probationary follow-up (45/92 recruits) showed that most health/fitness improvements declined after graduation. From academy graduation to probationary follow-up, recruits' physical activity decreased and TV screen time increased significantly, leading to a lower healthy lifestyle score (median, 4-3). After multivariate adjustments, the recruits' diastolic blood pressure increased by 2 mm Hg per measuring time throughout the study period. Conclusions Fire academy training improved recruits' select health and fitness measurements, but the benefits dissipated as probationary firefighters, and blood pressures increased throughout the study period. Further interventions regarding blood pressure and to maintain training benefits after joining fire departments are warranted.
Keywords: Occupational medicine; Body fat; Push-up; Healthy lifestyle; Blood pressure